Legal aspects of preventing and combating political corruption in Ukraine - Корчак, Наталія Миколаївна; Корчак, Ярослав (Київський національний університет імені Тараса Шевченка, 2021)
The purpose of the article is to comprehensively study political corruption as a phenomenon of social life in terms of legal aspects of its prevention and counteraction. The content of the publication is determined by the specifics of the subject of research and reflects the interdisciplinary approach to the disclosure of the topic. The article presents a comprehensive study of political, managerial and legal aspects of understanding political corruption. Emphasis is placed on the essence (nature) of political corruption as a phenomenon of the political process, and therefore - on the lack of a common conceptual understanding of the concept of "political corruption". It is emphasized that the concepts of "corruption" and "political corruption" are not identical in content or legal characteristics. The political aspect of corruption is an insufficient basis for extending the legal signs of corruption to actions that have signs of political corruption. It is argued that the task of legal science is to identify the causes, establish the preconditions and find the most effective measures to prevent and specify the means of combating political corruption. It is established that, unlike corrupt acts, types of behavior in the field of political corruption are not covered by legal liability measures. This is due to the lack of legal definition of "political corruption" in the current legislation. However, within the framework of normative regulation of relations in the field of state funding of political parties, a legal mechanism for preventing political corruption in Ukraine has been formed and operates. This led to the conclusion that due to the establishment of requirements and restrictions on the financing of political parties, the introduction of transparency and accountability of political parties and election campaigns, the legislator launched state control over the finances of political parties represented by the National Agency for Prevention of Corruption and to administrative or criminal liability for the relevant offenses. In view of this, emphasis is placed on the importance of understanding the legal aspects of political corruption, influencing political parties through finances, strengthening the financial discipline of political parties, improving the system of state control over the financing of political parties, and ensuring responsibility for violations in political financing. The scientific novelty of the article is the legal analysis of actions in the field of political corruption in terms of the introduction of legal mechanisms to prevent its manifestations. The practical significance of the article is related to the possibility of further use of its materials in the educational process, conducting interdisciplinary research on the phenomenon of political corruption and forming proposals for improving the legislative mechanisms of state control over the financial activities of political parties.

Мета статті полягає у комплексному дослідженні політичної корупції як явища соціального життя з точки зору правових аспектів її запобігання та протидії. Зміст публікації обумовлений специфікою предмета дослідження та відбиває міждисциплінарний підхід до розкриття теми. У статті представлене комплексне дослідження політико-управлінських та правових аспектів розуміння політичної корупції. Акцентовано увагу на сутності (природі) політичної корупції як феномена політичного процесу, а відтак - на відсутності єдиного концептуального розуміння поняття «політична корупція». Наголошено, що поняття «корупція» та «політична корупція» не є тотожними ні за змістом, ні за правовими характеристиками. Політичний аспект корупції є недостатньою підставою для поширення юридичних ознак корупції на дії, що мають ознаки політичної корупції. Аргументовано, що завданням юридичної науки є виявлення причин, встановлення передумов та знаходження найбільш ефективних заходів запобігання та конкретизація засобів протидії політичній корупції. Встановлено, що, на відміну від корупційних діянь, види поведінки у сфері політичної корупції, не охоплені заходами юридичної відповідальності. Це пояснюється відсутність у чинному законодавстві юридичного визначення поняття «політична корупція». Проте, в рамках нормативної регуляції відносин в сфері державного фінансування політичних партій сформовано і діє правовий механізм запобігання політичній корупції в Україні. Це дозволило дійти висновку, що через встановлення вимог та обмежень у сфері фінансування політичних партій, запровадження прозорості та підзвітності політичних партій і виборчих кампаній, законодавець запустив в дію процеси здійснення державного контролю за фінансами політичних партій в особі Національного агентства з питань запобігання корупції та механізми притягнення до адміністративної чи кримінальної відповідності за відповідні правопорушення. З огляду на це акцентується увага на важливості розуміння правових аспектів політичної корупції проблематики впливу на політичну партію через фінанси, посилення фінансової дисципліни політичних партій, удосконалення системи державного контролю зафінансуванням статутної діяльності політичних партій, а такожзабезпечення невідворотності відповідальності за порушення у сфері політичногофінансування. Наукова новизна статті полягає у здійсненні правового аналізу дій у сфері політичної корупції в аспекті запровадження правових механізмів запобігання її проявів. Практична значимість статті пов’язана з можливістю подальшого використання її матеріалів у навчальному процесі, проведенні міждисциплінарних досліджень феномену політичної корупції та формування пропозицій щодо удосконалення законодавчих механізмів державного контролю за фінансовою діяльністю політичних партій
Запобігання та протидія політичній корупції: правовий аспект
Keywords: політична корупція; державний контроль; запобігання та протидія; правові механізми; фінансування партій; political corruption; state control; prevention and counteraction; legal mechanisms; party financing